GUILLOTINE AND GOMCO CLAMP TECHNIQUE ON CIRCUMCISION - Alfi Mulia, Yusuf; Tusta Adiputra, Putu Anda (E-Jurnal Medika Udayana, 2013)
Circumcision is an action disposal of part or all prepusium dicks with a certain goal. Circumcision surgical procedure is most commonly done in men, because sirkumsisi done routinely for religious and culture reasons. Level circumcision occurs in among some races, 81 % in White; 65 % African-American, 54 % in Hispanic. Before doing an sirkumsisi, there are some stages covering preparation and anaesthetic. Techniques frequently used is guillotine and gomco clamp technique. On both this technique has advantages and disadvantages.
Keywords: circumcision, guillotine, gomco clamp